Screening for nutritional risk in hospitalized children: comparison of two instruments - Dwi Novianti; Tiangsa Sembiring; Sri Sofyani; Tri Faranita; Winra Pratita (Indonesian Pediatric Society, 2017)
Background Malnutrition in hospitalized children has negative impact on morbidity, mortality, length of stay, and health-care cost. A simple screening tool is needed to detect hospital malnutrition risk in children.Objective To compare the level of agreement of the Screening Tool for Malnutrition in Pediatrics (STAMP) and Pediatric Nutritional Risk Score (PNRS) with anthropometric measurements, as screening tools for hospital malnutrition in children.Methods A cross-sectional study was conducted from February to July 2014 in the Pediatric and Surgery Wards at H. Adam Malik Hospital, Medan, North Sumatera. Inclusion criteria were children aged 2 to 18 years who were hospitalized for more than 72 hours. Subjects were screened using STAMP and PNRS, and underwent anthropometric measurement on admission. The weight measurements were repeated on the 3rd and 7th days, and just before discharge. The STAMP and PNRS results were compared in terms of level of agreement with anthropometric measurements. Data were analyzed by Kappa value and Spearmanâ€™s correlation test.Results A total of 127 children were screened with both instruments. The PNRS had slight agreement with hospital malnutrition prevalence (Îº=0.175; P=0.028), while STAMP had notÂ (Îº=0.080; P=0.193). Both screening tools had weak positive correlations with length of stay, but the correlation was stronger for PNRS than for STAMP (r=0.218; P=0.014 vs. r=0.188; P=0.034, respectively). The prevalence of hospital malnutrition was 40.9%.Â Conclusions The PNRS screening tool has slight agreement with anthropometric measurement for identifying hospital malnutrition risk in children.